Who says "Ps get Degrees"? Examining the Profile of Undergraduate Students Maintaining High Achievement at University. - Lydster, Cameron (Student Success v.15 n.2 p.23-33 https://doi.org/10.5204/ssj.3402, 2024)
The circumstances associated with high levels of achievement in undergraduate studies has not been thoroughly explored in the Australian context. This study investigated factors predicting high academic achievement, defined as maintaining a Distinction average, at undergraduate level. Findings revealed several factors that predicted achievement after two semesters of study. These factors included essay writing skills, with students having satisfactory writing 5.16 times more likely to maintain a Distinction average compared to those with below satisfactory writing; faculty, with students enrolled in Health Sciences 4.63 times more likely compared to students from other faculties; language background, with English-speaking background students 1.67 times more likely compared to English as an additional language or dialect (EAL/D) students; gender, with females 1.45 more likely compared to males; and age, with older students 1.03 times more likely to achieve high performance compared to younger students. Creating a profile of students likely to excel academically assists decision makers in allocating resources to students less likely to achieve. This research opens the door to further studies investigating whether these factors play a role in predicting student achievement at university. [Author abstract]